2018
DOI: 10.1016/j.jvs.2017.06.086
|View full text |Cite
|
Sign up to set email alerts
|

Association of arterial calcification with chronic limb ischemia in patients with peripheral artery disease

Abstract: PAC is independently associated with increased ischemia categories in patients with peripheral artery disease. Further research aimed at understanding the relationship between arterial calcification and worsening limb ischemia is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 55 publications
3
46
1
Order By: Relevance
“…In this study, the total LEACS was associated with the total LEASI, indicating that the extent of arterial stenosis could be better predicted by the degree of calcification. This finding is supported by several similar observations [ 23 , 27 ]. The internal diameter of blood vessels in the normal human body can be maintained through a compensatory increase in arterial perimeter, but Sigrist et al [ 28 ] found that decreased arterial compliance is associated with femoral arterial calcification in dialysis patients, which might eventually lead to vascular stenosis.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the total LEACS was associated with the total LEASI, indicating that the extent of arterial stenosis could be better predicted by the degree of calcification. This finding is supported by several similar observations [ 23 , 27 ]. The internal diameter of blood vessels in the normal human body can be maintained through a compensatory increase in arterial perimeter, but Sigrist et al [ 28 ] found that decreased arterial compliance is associated with femoral arterial calcification in dialysis patients, which might eventually lead to vascular stenosis.…”
Section: Discussionsupporting
confidence: 91%
“… 4 Both intimal and medial calcification contribute to arterial wall stiffness, which leads to the vessel recoil and restenosis seen after endovascular interventions. 2 , 5 – 7 Although considerable progress in endovascular therapy has been made over the past decade, controversy still exists among physicians as to the best endovascular strategy for patients with symptomatic disease of the infrapopliteal arteries, particularly those with significant calcification.…”
Section: Introductionmentioning
confidence: 99%
“…Abating fatal cardiovascular disease (CVD) events among patients with atherosclerosis, chronic kidney disease, diabetes and the aging population remains an imperative clinical challenge. CVD induces major arterial occlusions and stiffening, which can be largely driven by the development of vascular calcification, and the associated hemodynamic consequences cause high rates of hypertension, myocardial infarction, stroke and lower-limb ischemia [ 1 , 2 ]. The mortality rate of patients with chronic kidney disease (CKD) alone accounts for 50% of premature deaths while additionally patients with peripheral arterial disease are predisposed to lower limb amputations [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%